ENVIRONMENTAL PROBLEMS OF COTTON GINNING ENTERPRISES - Eshnazarov D. A.; Jalilova M. S; Urmanov N. T (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides information on dust emitted from ginneries and discusses the properties, composition, and size of these powders. The article also provides information on the negative impact of dust collection devices on cleaning efficiency based on dust properties.